Adoption of Empowerment Deduced from the Islamic Management Thought As a Strategy for Management Development: A Field Study on the Saudi Ministry of Education - AL Idroos, Agadeer (The Arab Journal of Administration, 2018)
The study aims to draw the administrative empowerment strategy; detects dimensions and administrative requirements of Islamic Thought, and validate the findings of scientists from the West for the principles of administrative empowerment is only an echo of what in the Islamic Management Though. The study used the fundamentalist deductive approach in the analysis of the content of the verses and the development dimensions and requirements relating to the administrative empowerment, and use descriptive method Correlative to see a relationship between the empowerment of employees and management development prove that administrative empowerment in the Islamic Management Thought A strategy for Management Development: Through the exercise of Commitment to working in the dimensions of empowerment requirements (power and honesty) Lead to the development of administrative power: associated with the preparation of the potential of the individual worker and the physical capacity. Honesty: linked to the ideological commitmen of the individual and behavioral. two dimensions and thus complement each other. In force after it realized the need for achievement, and after.honesty factor means of force application by doing the behavior of the organization There is a significant correlation between moral administrative empowerment Abstract of Islamic Thought administrative, and management development There is a moral effictiveness of administrative empowerment processes which is Abstractted from Islamic Thought administrative, and management development. There are no moral differences of statistically significant between empowerment of employees and management development to the variable of academic qualification and years of experience> Field side results proved that the administrative empowerment extracted from Islamic Thought in place already without the knowledge of members of the Saudi society as linkage of Islam. And this confirms that the approach of the Koran being on the scope of the possible and the compatibility of Islam and the innate nature without discomfort. Commitment to the Islamic way leads to scientific progress and development, requires a radical change in the patterns and methods of application of empowerment in education institutions.